Can a click buy a little happiness? The impact of business-to-consumer e-commerce on subjective well-being - Fabio Sabatini (Economics and Econometrics Research Institute (EERI), 2011)
This paper presents the first empirical investigation into the effect of e-shopping on subjective well-being. The analysis relies on a nationally and regionally representative dataset from Italy (n = 4,130) drawn from the 2008 wave of the Survey of Household Income and Wealth (SHIW) carried out by the Bank of Italy. Probit, OLS regressions and instrumental variables estimates show that e-shopping is strongly and positively associated with subjective well-being.
Keywords: I31; E2; Z19; L86; 330; Happiness; subjective well-being; Internet; business-to-consumer e-commerce; B2C; e-shopping; instrumental variables; Italy